Effect of Canyons on a Fire Propagating Laterally Over Slopes - Rodrigues, André; Ribeiro, Carlos; Raposo, Jorge; Viegas, Domingos Xavier; André, Jorge (Frontiers in Mechanical Engineering, 2019)
In this paper the problem related with a fire front propagating laterally on a slope with a nearby canyon is presented. The presence of the canyon can modify the intensity of the fire and create a difficult situation for elements involved in fire suppression. When a fire propagating laterally in a slope enters in the canyon, a rapid increase in the fire’s rate of spread occurs and a strong convective activity is generated due to the burning inside the canyon. The convective flow generated will then induce a change in the propagation of the fire in the slope. In certain conditions the rate of spread and the intensity of the fire will be strongly increased. This type of extreme fire behaviour is referred to as eruptive fire behaviour (or blow-up) and usually happens over slopes or in canyon configurations. In this study, we analysed the results of laboratory-scale experiments that model a fire spreading latterly over a slope and then enter a canyon that is embedded in the slope. Three configuration parameters were used in the experiments. The first is the inclination  of the slope, the second is the orientation of the axis of the canyon and the third is the angle  of the ignition line. The fire spread is very complex and dynamic resulting in situations in which very high values of the ROS can be reached for several configurations, creating dangerous situations for firefighters.